1995
DOI: 10.1021/ed072p987
|View full text |Cite
|
Sign up to set email alerts
|

Success on Algorithmic and LOCS vs. Conceptual Chemistry Exam Questions

Abstract: The performance of freshman science, engineering, and in-service teacher students in three Israeli and American universities on algorithmic, lower-order cognitive skills (LOCS), and conceptual chemistry exam questions was investigated. The driving force for the study was an interest in moving chemistry instruction from an algorithm-oriented factual recall approach dominated by LOCS to a decision-making, problem-solving, and critical thinking approach dominated by higher-order cognitive skills (HOCS). Students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
1
11

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 5 publications
(14 reference statements)
8
103
1
11
Order By: Relevance
“…En este sentido, la taxonomía planteada por Smith et al (2010) mantiene, como valor añadido, el intento de integrar distintas perspectivas. Así, serían las preguntas de Definición las que implicarían un mayor grado de recuerdo o retención de información, mientras que las Conceptuales serían las que incorporarían un mayor grado de demanda tipo HOCS, en términos de Zoller (Zoller et al, 1995), y de destrezas de análisis, evaluación y creación, en términos de Anderson y Krathwohl (2001). Es precisamente este intento integrador el que, como veremos, nos ha llevado a utilizar dicho esquema como uno de los criterios de clasificación empleados en el estudio.…”
Section: Conceptual (C)unclassified
See 3 more Smart Citations
“…En este sentido, la taxonomía planteada por Smith et al (2010) mantiene, como valor añadido, el intento de integrar distintas perspectivas. Así, serían las preguntas de Definición las que implicarían un mayor grado de recuerdo o retención de información, mientras que las Conceptuales serían las que incorporarían un mayor grado de demanda tipo HOCS, en términos de Zoller (Zoller et al, 1995), y de destrezas de análisis, evaluación y creación, en términos de Anderson y Krathwohl (2001). Es precisamente este intento integrador el que, como veremos, nos ha llevado a utilizar dicho esquema como uno de los criterios de clasificación empleados en el estudio.…”
Section: Conceptual (C)unclassified
“…Estas preguntas de tipo "Algorítmicas" eran, en su totalidad, de carácter cuantitativo, y centradas en la resolución de problemas tipo. Son por tanto preguntas que podríamos clasificar como LOCS en los términos propuestos por Zoller et al (1995). No se incluyen, sin embargo, otro tipo de 466 preguntas cuantitativas de carácter más abierto y orientadas a mostrar la creatividad de los estudiantes y su capacidad para resolver problemas novedosos, no necesariamente complejos.…”
Section: Tipología De Preguntasunclassified
See 2 more Smart Citations
“…Sawrey showed that difficulties with conceptual items were found for students with both high and low performance on traditional quantitative items (3). Nakhleh and coworkers carried out a series of studies that further established the gap between conceptual understandings and algorithmic problem solving skills and sought pedagogies to mediate that gap (4)(5)(6)(7)(8). More recent work by Niaz (9) and Cracolice (10) continues to identify ways in which conceptual knowledge lags behind algorithmic knowledge in chemistry students.…”
Section: Introductionmentioning
confidence: 99%